Microwave-antenna induced in situ synthesis of Cu nanowire threaded ZIF-8 with enhanced catalytic activity in H2 production. Issue 14 (22nd March 2016) - Zhang, Dieqing; Liu, Peijue; Xiao, Shuning; Qian, Xufang; Zhang, Hui; Wen, Meicheng; Kuwahara, Yasutaka; Mori, Kohsuke; Li, Hexing; Yamashita, Hiromi
Abstract : A novel CuNW/ZIF-8 catalyst with high activity and stability in H2 production from NH3 BH3 hydrolysis was synthesized via a microwave-antenna strategy. Abstract : A microwave-antenna strategy was developed for the in situ synthesis of Cu nanowire (CuNW) threaded ZIF-8. The CuNWs acted as microwave-antennas to generate surface "super hot" dots. The high temperature of "super hot" dots induced adsorption and coordination of metal ions and organic ligands, followed by in situ assembly and crystal-growth along the CuNWs. This catalyst exhibited high activity and stability in H2 production via NH3 BH3 hydrolysis owing to the synergetic effect. The CuNWs supplied a rapid electron transfer channel while ZIF-8 assembled on the CuNWs offered a large capacity for adsorbing reactants and channels for rapidly transferring H − /H + ions toward Cu active sites. Other one-dimensional threaded MOFs, including CuNW threaded MOF-5 and UIO-66, or carbon nanotube threaded ZIF-8 and ZIF-67 could also be prepared using the microwave-antenna strategy.